Reliability of heart rate variability threshold and parasympathetic reactivation after a submaximal exercise test - Carlos Janssen Gomes da Cruz; Paloma da Silva Rolim; Deleon de Souza Pires; Christopher Marcos Oliveira Mendes; Gabriel Monteiro de Paula; Luiz Guilherme Grossi Porto; Giliard Lago Garcia; Guilherme Eckhardt Molina
Abstract The objective of this study was to evaluate reproducibility of heart rate variability threshold (HRVT) and parasympathetic reactivation in physically active men (n= 16, 24.3 ± 5.1 years). During the test, HRVT was assessed by SD1 and r-MSSD dynamics. Immediately after exercise, r-MSSD was analyzed in segments of 60 seconds for a period of five minutes. High absolute and relatively reproducible analysis of HRVT were observed, as assessed by SD1 and r-MSSD dynamics (ICC = 0.92, CV = 10.8, SEM = 5.8). During the recovery phase, a moderate to high reproducibility was observed for r-MSSD from the first to the fifth minute (ICC = 0.69-0.95, CV = 7.5-14.2, SEM = 0.07-1.35). We conclude that HRVT and r-MSSD analysis after a submaximal stress test are highly reproducible measures that might be used to assess the acute and chronic effects of exercise training on cardiac autonomic modulation during and/or after a submaximal stress test.